Breast feeding is associated with postpartum smoking abstinence among women who quit smoking due to pregnancy - Kendzor, Darla E. (Oxford University Press, 2010)
INTRODUCTION: The purpose of this study was to characterize the relationship between breast feeding and postpartum smoking abstinence among women who quit smoking due to pregnancy and who were participating in a randomized clinical trial of an intervention designed to prevent postpartum relapse. METHODS: A total of 251 women were enrolled in the intervention between 30 and 33 weeks postpartum and were followed through 26 weeks postpartum. Participant characteristics were assessed at the prepartum baseline visit, any breast feeding was assessed at 8 weeks postpartum, and smoking abstinence was assessed at 8 and 26 weeks postpartum. RESULTS: Although 79.1% of participants intended to breast feed, only 40.2% reported breast feeding at 8 weeks postpartum. Characteristics associated with breast feeding at 8 weeks postpartum included Caucasian race/ethnicity, greater education, higher household income, and being married/living with a significant other. Logistic regression analysis indicated that breast feeding at 8 weeks postpartum was significantly associated with smoking abstinence at 8 weeks postpartum, odds ratio (OR) = 7.27 (95% CI = 3.27, 16.13), p < .001. Breast feeding at 8 weeks postpartum was also associated with abstinence at 26 weeks postpartum after controlling for smoking status at 8 weeks postpartum, OR = 2.64 (95% CI = 1.14, 6.10), p = .02. DISCUSSION: Encouraging breast feeding among women who quit smoking due to pregnancy may facilitate postpartum smoking abstinence while increasing adherence to current infant feeding guidelines.